can't add these numbers till you get their powers of 10 to match. So, doing that, we get
6.91x10^-2 - 0.24x10^-2 = 6.67x10^-2
What is (6.91 x 10-2 power) + (2.4 x 10-3 power) ? Express your answer in scientific notation.
3 answers
Uhm, if you want it correct then do these step,
(6.91 x 10-2 power) + (2.4 x 10-3 power)= 0.691+2.4 = 3.091 x 10-3 power
we move . from 6. to 0.6 because the power isn't the same so we add the lower power by moving dots and +1 the power or -1 if Neg^.
(6.91 x 10-2 power) + (2.4 x 10-3 power)= 0.691+2.4 = 3.091 x 10-3 power
we move . from 6. to 0.6 because the power isn't the same so we add the lower power by moving dots and +1 the power or -1 if Neg^.
qwertyuiop